Australian School Student Perceptions of Effective Anti-tobacco Health Warnings - Drovandi, Aaron; Teague, Peta-Ann; Glass, Beverley; Malau-Aduli, Bunmi (Frontiers in Public Health, 2018)
Background: Recent research posits that anti-tobacco health warnings on cigarette packaging may gradually lose their effectiveness in dissuading adolescents from tobacco products several years after implementation. Health warnings on individual cigarette sticks represent a novel warning medium, and may further educate adolescents on the dangers associated with smoking, and reduce tobacco experimentation amongst this vulnerable population. Methods: In an online survey of school students in Queensland, Australia, participants were requested to rate (on 5-point Likert scales) and comment on the perceived effectiveness of current cigarette packaging warnings, and 12 text warnings on cigarette sticks, in preventing non-smokers from smoking, and encouraging current smokers to quit. The warnings were divided into four themes to establish the most effective types of anti-tobacco messages: mortality statistics, health condition consequences, social and financial consequences, and supportive messages. These themes were based on current anti-tobacco interventions within Australia, and the rising cost of tobacco products, and designed to align with the Health Belief Model. Results: Participants (N=150; Age=15-18) from five schools completed the survey, and generally viewed current packaging warnings as ‘gross’ and ‘disgusting’, and rating them as somewhat effective in preventing non-smokers from smoking. Current warnings were however considered less effective in prompting current smokers to quit with participants describing them as being un-relatable to teenagers, and smokers as having become desensitised to the warnings used. One theme of cigarette-stick warning (mortality statistics) was rated as significantly more effective (p <.001) than current cigarette packaging, with an odds ratio (OR) of 2.77 (95% confidence interval [CI]: 1.67-4.62). Overall, warnings were considered to be 4.71 times (95%CI: 2.72-6.43, p <.001) more effective on non-smokers than on smokers. Over three-quarters of participants supported using health warnings on individual cigarette sticks. Conclusions: Current cigarette packaging warnings have retained some effectiveness in dissuading adolescents from smoking, though novel and thought-provoking text-only warnings on cigarette sticks may serve as an additional intervention in reducing tobacco use. Further research requires identification of the most effective warnings, and the perceptions of a more diverse participant base.